DNA double-strand break repair is impaired in presenescent Syrian hamster fibroblasts - Solovjeva, Ljudmila (BMC Mol Biol, 2015)
BACKGROUND: Studies of DNA damage response are critical for the comprehensive understanding of age-related changes in cells, tissues and organisms. Syrian hamster cells halt proliferation and become presenescent after several passages in standard conditions of cultivation due to what is known as «culture stress». Using proliferating young and non-dividing presenescent cells in primary cultures of Syrian hamster fibroblasts, we defined their response to the action of radiomimetic drug bleomycin (BL) that induces DNA double-strand breaks (DSBs). RESULTS: The effect of the drug was estimated by immunoblotting and immunofluorescence microscopy using the antibody to phosphorylated histone H2AX (gH2AX), which is generally accepted as a DSB marker. At all stages of the cell cycle, both presenescent and young cells demonstrated variability of the number of gH2AX foci per nucleus. gH2AX focus induction was found to be independent from BL-hydrolase expression. Some differences in DSB repair process between BL-treated young and presenescent Syrian hamster cells were observed: (1) the kinetics of gH2AX focus loss in G0 fibroblasts of young culture was faster than in cells that prematurely stopped dividing; (2) presenescent cells were characterized by a slower recruitment of DSB repair proteins 53BP1, phospho-DNA-PK and phospho-ATM to gH2AX focal sites, while the rate of phosphorylated ATM/ATR substrate accumulation was the same as that in young cells. CONCLUSIONS: Our results demonstrate an impairment of DSB repair in prematurely aged Syrian hamster fibroblasts in comparison with young fibroblasts, suggesting age-related differences in response to BL therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12867-015-0046-4) contains supplementary material, which is available to authorized users.